GRATITUDE AS A PREDICTOR OF SENSE OF SCHOOL BELONGING IN SENIOR HIGH SCHOOL STUDENTS - Ahmad Fadil Fadil; Tri Anggono; Moses Idongesit Peters; Masuma Parvin (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
The value of a school sense Students' sense of belonging at school positively impacts their lives, encouraging the growth of empathy, optimism, self-worth, and subjective happiness. However, in reality, when students feel a lack of SoSB, this can lead to the emergence of problematic behaviour in the school environment. Therefore, the importance of gratitude in each individual to improve students' SoSB must be addressed. This research aims to determine how thankfulness influences high school students' feelings of belonging. With a population of 225 individuals, the study's participants were high school students between 15 and 18. With a straightforward random sampling approach, 144 high school students 45 (31.3%) boys and 99 (68.8%) females were chosen to make up the research sample. The gratitude scale, with 11 items (? = 0.78), and the sense of school belonging scale, with 18 items (? = 0.91), were the instruments utilized in this study. They were distributed via the Google Form platform. Data analysis was conducted using simple Linear regression, and the research hypothesis supports the existence of a positive and statistically significant influence between gratitude on the sense of school belonging, the value of count = 7.857 ? 1.976 = Ttable and (p ? 0.01) with a coefficient of determination R2 of 30.3%. The study concludes that thankfulness influences high school students' sense of school belonging positively by 30.3%; other factors that were not included in the study are responsible for the remaining variation.